Influences of the dip-coated BN interface on mechanical behavior of PIP-SiC/SiC minicomposites. Issue 11 (1st June 2021) - Xu, Hao; Li, Lu; Zheng, Ruixiao; Ma, Chaoli
Abstract: SiC/SiC minicomposites with BN interfaces were fabricated by a two-step route comprising dip-coating and polymer impregnation and pyrolysis (PIP). The thickness of the dip-coated BN interface was in the range of 76–300 nm, which was adjusted by dipping times. The influences of BN interface thickness on the mechanical behavior of the as-fabricated SiC/SiC minicomposites were investigated. The mechanical properties of SiC/SiC composites were improved by introducing BN interfaces, which showed an optimized tensile strength distribution with a higher Weibull modulus m . The optimal mechanical properties could be obtained in SiC/BN/SiC-2 samples with the BN interface thickness of ~160 nm. The variation trend of tensile strengths caused by the increasing interface thickness was analyzed using a probabilistic-statistical model. Especially, both the interface delamination caused by the secondary crack and the fiber Weibull parameter m fiber influenced by the BN interface coating were considered in the probabilistic-statistical model, leading to a better matching between the experimental results and the model simulation. Microstructure characterization combined with numerical analysis showed that the dip-coated BN interface with appropriate thickness played an important role in improving the mechanical properties of SiC/SiC minicomposites. The results indicated that both the ability of crack deflection of interfaces and the fiber in-situ strengths should be considered in the interface design of SiC/SiC composites.